Sediaan Gel dari Kombinasi Ekstrak Buah Gandaria (Bouea macrophylla Griff.) dan Ekstrak Belimbing Wuluh (Averhoa bilimbi L) dan Bioaktivitasnya - Jayantie, Dhyneu Dwi; Khaerunnisa, Arini; Renaldy, Renaldy; Suryani, Nani; Rudiana, Tarso (ALCHEMY:Journal of Chemistry, 2024)
Melanin is the main pigment thfunctions to protect the skin from exposure to ultraviolet light, excessive melanin synthesis can cause skin hyperpigmentation. A. bilimbi and B. macrophylla fruits have bioactive compounds such as phenolics, flavonoids that function as antioxidants and tyrosinase inhibitors. This study aims to formulate a gel preparation of a combination of fruit extracts of A. bilimbi and B. macrophylla, test antioxidant activity using the DPPH method, and test tyrosinase inhibition enzymes. Three formulas were made, namely F0 (Basis), FI (50x extract), and FII (100x extract). Physical evaluation includes organoleptic, homogeneity, pH, adhesion, spreadability, viscosity, viscosity and irritation. Test of antioxidant activity and tyrosinase enzyme inhibition. Then the data were analyzed descriptively and statistically. The results of the evaluation of homogeneous preparations, dispersion, pH, viscosity, mandatory, meet the standards. Adhesion below standard, irritation test (mild irritation). The results of IC50 antioxidants were F0 (2,352 ppm), FI (1,448 ppm), FII (419,74 ppm) and gel brand x (77,429 ppm). The results of the tyrosinase inhibition test were the highest concentration of 10% F0 (7.828%), a concentration of 10% FI (18.245%), a concentration of 10% FII (25.814) kojic acid gel (brand x) as a comparison with a concentration of 10% (51.211%). The higher the concentration used, the greater the inhibition of the tyrosinase enzyme produced